National survey of feasibility of NIV trials for management of children with bronchiolitis. Issue 1 (27th October 2020) - Rosala-Hallas, Anna; Jones, Ashley P; Bedson, Emma; Compton, Vanessa; Fernandes, Ricardo M; Lacy, David; Lyttle, Mark D; Peak, Matthew; Thorburn, Kent; van Miert, Clare; Woolfall, Kerry; McNamara, Paul S
Abstract : Background: Bronchiolitis is a major cause of admission to hospital in children. Non-invasive ventilation (NIV) support with continuous positive airway pressure (CPAP) or high-flow nasal cannula (HFNC) oxygen is routinely used for infants in the UK with bronchiolitis. Objective: To establish UK paediatric practice regarding management of bronchiolitis, and to explore issues pertinent to the design of a potential future randomised controlled trial of NIV. Design: Screening logs were completed in hospitals in England capturing information on paediatric bronchiolitis admissions. An online national survey of clinical practice was disseminated to healthcare professionals (HCPs) across the UK to ascertain current management strategies. Results: Screening logs captured data on 393 infants from 8 hospitals. Reasons for admission were most commonly respiratory distress and/or poor fluid intake. Oxygen was administered for 54% of admissions. Respiratory (CPAP and HFNC) and non-respiratory support administered varied considerably. The national survey was completed by 111 HCPs from 76 hospitals. Data were obtained on criteria used to commence and wean NIV, responsibilities for altering NIV settings, minimum training requirements for staff managing a child on NIV, and numbers of trained staff. Most centres were interested in and capable of running a trial of NIV, even out of normal office hours. Conclusions: Respiratory and non-respiratory management of bronchiolitis in UK centres varies widely. A trial of HFNC oxygen therapy in this group of patients is feasible and HCPs would be willing to randomise patients into such a trial. Future work should focus on defining trial eligibility criteria.